The Use of Historical Fiction in the Language Classroom: A Pedagogical Proposal for Teachers of English. Issue 1 (13th June 2018) - Shin, Jaran
Abstract : In the context of globalization, teachers of English are no longer expected to cultivate learners' functional and communicative abilities alone; instead, the profession also requires teachers to acknowledge that teaching English is a political act, to discuss how power relations are negotiated through language, and to enrich learners' historical and political consciousness. This article proposes that teachers of English can use historical fiction as a way to help learners be more cognizant of historical and political realities that they are part of—in addition to becoming more familiar with the English language. This pedagogical suggestion begins with the rationale for using historical fiction in teaching English. This rationale lends itself to a series of classroom tasks, which are designed to contribute to learners' awareness of how historical realities are shaped in/through language and how the construction of historical representation reinforces particular memories and discourses. This process will eventually help learners of English reflect on who they have been, understand who they are now, and envision who they want to be.